Letter of Introduction - Carpenter, Michael J (Borders in Globalization Review, 2023)
The long-awaited and much anticipated new issue of Borders in Globalization Review is here! This outstanding collection of scholarship and artwork enriches border studies and cultural reflections on (and against) borders ...